Implementation of Public Relations Management in Increasing Parental Participation in Elementary Schools - Hafifatul Mukarohmah, Ayun; Fatimah, Hj. Siti (Jurnal Multidisiplin Indonesia, 2023)
Public relations management in increasing the participation of student parents is one way of fostering and developing harmonious relationships between schools and school parents in establishing close relationships with school parents. The role and activities of good internal and external relations determine the success of an educational institution in achieving its mission and goals. This research uses a qualitative approach to present, analyze, and interpret to solve existing problems based on data. This qualitative method seeks to understand and interpret the meaning of an event involving human behavior in certain situations according to the researcher's perspective. The research results show that public relations management wants to improve the participation of the parents of students with the factors that influence it, namely the type of age class and the parents' livelihood. The steps taken to increase the participation of the parents of students are the first planning stage, which is how the school prepares the school activity program. The second stage is the implementation, which must be done by establishing good communication. The third stage, namely evaluation, aims to increase guardian participation.